Jambi City Tourism Information System Design - Milano, Rezagi; Tanto, Tanto (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
The very rapid development of technology helps a lot in terms of disseminating information to be faster, more accurate, and not limited by place and time. Technology in the tourism sector is not only used as a promotional medium, but technology is also a learning medium for entrepreneurs in the tourism sector so it is important for the tourism sector to have an information system as a medium for disseminating information. The Jambi City Tourism Information System is an information system that contains a collection of information data that summarizes information about the region, province or tourism place in the city of Jambi which is compiled in a web-based information system, with this information system it can make it easier for the public to obtain information. , accelerating the service of information sources. The design of the tourism information system in the city of Jambi is built in a web-based form with system design assisted by several tools such as the programming language PHP, Javascript, MySQL, Xampp, and Adobe Dreamweaver.